2018
DOI: 10.1038/s41467-018-04860-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic strain determination using fibre-optic cables allows imaging of seismological and structural features

Abstract: Natural hazard prediction and efficient crust exploration require dense seismic observations both in time and space. Seismological techniques provide ground-motion data, whose accuracy depends on sensor characteristics and spatial distribution. Here we demonstrate that dynamic strain determination is possible with conventional fibre-optic cables deployed for telecommunication. Extending recently distributed acoustic sensing (DAS) studies, we present high resolution spatially un-aliased broadband strain data. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
236
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 449 publications
(245 citation statements)
references
References 55 publications
9
236
0
Order By: Relevance
“…Here, we restrict our focus to a single commercial instrument, the Silixa iDAS (Version 2), which is a time domain, single‐pulse, phase‐based DAS instrument (Parker et al, ). This particular DAS instrument is among the more widely utilized in the field of earthquake seismology (Ajo‐Franklin et al, ; Jousset et al, ; Lindsey et al, ; Wang et al, ; Yu et al, ). The following discussion of the relationship between ground motion and DAS data is a synthesis of many works including Bakku (), Bóna et al (), Dean et al (), Grattan and Meggitt (), Hartog (), Kreger et al (), Karrenbach et al (), Masoudi and Newson (), Posey et al (), Parker et al (), and Willis et al (), as well as U.S. patents on the technology (Farhadiroushan et al, ).…”
Section: The Das Measurement Principlementioning
confidence: 99%
See 3 more Smart Citations
“…Here, we restrict our focus to a single commercial instrument, the Silixa iDAS (Version 2), which is a time domain, single‐pulse, phase‐based DAS instrument (Parker et al, ). This particular DAS instrument is among the more widely utilized in the field of earthquake seismology (Ajo‐Franklin et al, ; Jousset et al, ; Lindsey et al, ; Wang et al, ; Yu et al, ). The following discussion of the relationship between ground motion and DAS data is a synthesis of many works including Bakku (), Bóna et al (), Dean et al (), Grattan and Meggitt (), Hartog (), Kreger et al (), Karrenbach et al (), Masoudi and Newson (), Posey et al (), Parker et al (), and Willis et al (), as well as U.S. patents on the technology (Farhadiroushan et al, ).…”
Section: The Das Measurement Principlementioning
confidence: 99%
“…Elevated DAS amplitude response at short periods could be caused by the style and degree of rigid coupling through which strain is transferred from the ground to the fiber. Coupling is a necessary condition for any seismometer (Lay & Wallace, 1995), yet many DAS studies have concluded that mechanical coupling of the fiber-optic to the ground had an impact on their results (Becker et al, 2017;Jousset et al, 2018;Lindsey et al, 2017;Wang et al, 2018;Willis et al, 2017;Yu et al, 2019). Coupling is a static feature of a DAS experiment (fiber array; DAS recording parameters) that should be assumed to not change over the duration of a typical geophysical campaign (days to months).…”
Section: 1029/2019jb018145mentioning
confidence: 99%
See 2 more Smart Citations
“…DFOS with Raman scattering has already been known as distributed temperature sensing and utilized for a host of hydrological and geothermal applications (Briggs et al, 2012;Carlino et al, 2016;Curtis & Kyle, 2011;Selker et al, 2006). Recently, by exploiting changes in Brillouin and Rayleigh scattering induced by external strains, the DFOS technology has been utilized for geohazard sensing including earthquake observations (Dou et al, 2017;Jousset et al, 2018;Lindsey et al, 2017) and landslide detection (Huntley et al, 2014;Lienhart, 2015;Michlmayr et al, 2017;Picarelli et al, 2015;Schenato et al, 2017). While a few studies have explored the feasibility of DFOS for subsidence and strata deformation sensing (Murai et al, 2013;Wu et al, 2015), the understanding of data collected from borehole-embedded FO cables has remained elusive and hence precluded its use in many contexts.…”
Section: Introductionmentioning
confidence: 99%